2021
DOI: 10.1007/s12061-021-09400-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the exposure of Black, Asian and other ethnic groups to COVID-infected neighbourhoods in English towns and cities

Abstract: Drawing on the work of The Doreen Lawrence Review—a report on the disproportionate impact of COVID-19 on Black, Asian and minority ethnic communities in the UK—this paper develops an index of exposure, measuring which ethnic groups have been most exposed to COVID-19 infected residential neighbourhoods during the first and second waves of the pandemic in England. The index is based on a Bayesian Poisson model with a random intercept in the linear predictor, allowing for extra-Poisson variation at neighbourhood … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Participants also discussed the impact of the intersection of demographic factors, including ethnicity, with other factors such as deprivation. In an exploration of exposure to COVID-19 within residential neighbourhoods, Harris and Brunsdon (11) found that Pakistani, Bangladeshi and Indian groups were disproportionately exposed to the COVID-19 virus in later waves of the pandemic which is likely to re ect the nature of employment of these groups who were more likely to work in public facing roles thereby increasing their risk of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Participants also discussed the impact of the intersection of demographic factors, including ethnicity, with other factors such as deprivation. In an exploration of exposure to COVID-19 within residential neighbourhoods, Harris and Brunsdon (11) found that Pakistani, Bangladeshi and Indian groups were disproportionately exposed to the COVID-19 virus in later waves of the pandemic which is likely to re ect the nature of employment of these groups who were more likely to work in public facing roles thereby increasing their risk of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The socioeconomic impacts of Covid have been experienced unequally in the United Kingdom and it has been argued that this reflects longstanding patterns of (health) inequalities (Bambra et al, 2020). It is well known that people who are poorer, with pre‐existing health conditions, from ethnic minorities, and resident in densely‐populated neighbourhoods have been at greater risk of catching and dying from the disease (Basellini et al, 2021; Blundell et al, 2020; Drefahl et al, 2020; Harris & Brunsdon, 2021; Hughes et al, 2021) in various European contexts. Moreover, these inequalities translate into complex geographies as the disease spreads through the population (Feng, 2021).…”
Section: Review Of Pandemic Responsesmentioning
confidence: 99%
“…Han et al (2020) examined the consequences of easing COVID-19 restrictions in five high-income countries in Asia Pacific and four in Europe, concluding that although the outcome of the pandemic crisis is still uncertain, countries should continue to learn from the experiences they face so as to limit the transmission of the virus and to protect vulnerable groups. Ultimately, it stands to reason that countries strive to make decisions about easing restrictions based on a combination of infection severity/mortality rate and on the multidimensional effects of restrictions (Harris & Brunsdon, 2021).…”
Section: Overview Of the First Wave Of Pandemic Crisis In The Europea...mentioning
confidence: 99%